2003
DOI: 10.1097/01.shk.0000055815.40894.16
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acids and Glucose Increase Neutral Endopeptidase Activity in Human Microvascular Endothelial Cells

Abstract: Neutral endopeptidase (NEP), a membrane-bound metallopeptidase enzyme that degrades neuropeptides, bradykinin, atrial natriuretic factor, enkephalins, and endothelin may regulate response to injury. We have previously demonstrated increased NEP localization and enzyme activity in diabetic wounds and skin compared with normal controls. We hypothesized that hyperlipidemia and hyperglycemia associated with type 2 diabetes mellitus may induce excessive NEP activity and thereby diminish normal response to injury. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 35 publications
1
44
0
Order By: Relevance
“…Because NEP has previously been demonstrated to be regulated by glucose and fatty acids 34 and NEP is produced by adipocytes, 35 it is conceivable that circulating NEP might be correlated with other features of the metabolic syndrome. This is the first study to determine the heritability of circulating NEP, which was estimated to be 22.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Because NEP has previously been demonstrated to be regulated by glucose and fatty acids 34 and NEP is produced by adipocytes, 35 it is conceivable that circulating NEP might be correlated with other features of the metabolic syndrome. This is the first study to determine the heritability of circulating NEP, which was estimated to be 22.7%.…”
Section: Discussionmentioning
confidence: 99%
“…Neprilysin (encoded by Nep , also known as Mme ) is a widely expressed plasma membrane peptidase with increased levels in metabolically altered states [13]. We and others have demonstrated that reducing neprilysin activity may be beneficial via improving insulin secretion [4] and sensitivity [57].…”
Section: Introductionmentioning
confidence: 99%
“…Neutral endopeptidase is found in many tissues, including vascular tissue, and its activity is increased by fatty acids and glucose in human microvascular cells (13)(14)(15)(16)(17). Interestingly, neutral endopeptidase activity has been shown to be activated by protein kinase C, which is increased in vascular tissues by diabetes (18,19).…”
mentioning
confidence: 99%